Investigation of Carbon Tax Pilot in YRD Urban Agglomerations—Analysis and Application of a Novel ESER System with Carbon Tax Constraints. (June 2016) - Fang, Guochang; Tian, Lixin; Fu, Min; Sun, Mei; Du, Ruijin; Liu, Menghe
Abstract: This paper attempts to explore the dynamic behavior of energy-saving and emission-reduction (ESER) system in Yangtze River Delta (YRD) urban agglomerations, which has not yet been reported in present literature. The novel YRD urban agglomerations carbon tax attractor is achieved. A scenario study is carried out. The results show that, the ESER system in YRD urban agglomerations is superior to the average case in China, in which the impacts on economic growth are almost the same. The economic property of YRD urban agglomerations is the main cause why the ESER system of YRD urban agglomerations being superior.